Effects of two devices on the surface electromyography responses of eleven shoulder muscles during Azarian in gymnastics - Bernasconi, S. M.; Tordi, N. R.; Parratte, B. M.; Rouillon, J. D. R.; Monnier, G. G. (The Journal of Strength and Conditioning Research, 2006)
Difficult elements of strength such as Azarian must be presented on the rings. Specific-muscles training may be realized with 2 devices, the Herdos and the Belt, both of which reproduce the competitive situation and allow many repetitions. The purpose of this study was therefore to compare the shoulder muscle activity during the performance of Azarian with each device. Our results show that muscles rhomboid, supraspinatus, deltoid (anterior, middle, and posterior parts), biceps brachii, and triceps brachii have significant (p < 0.05) higher root mean square value when gymnasts use the Belt compared with the Herdos. Although the Herdos and the Belt reproduce competitive movement, their muscle activities are quite different. The Herdos reduces the stress on the shoulder and elbow joints, whereas the Belt induces higher muscle activity and probably provides closer muscle synergisms to the rings.